Difference in the prevalence of intracardiac thrombus on the first presentation of atrial fibrillation versus flutter in the pediatric and congenital heart disease population. (5th November 2020) - Meziab, Omar; Marcondes, Luciana; Friedman, Kevin G.; O'Leary, Edward T.; Gurvitz, Michelle; VanderPluym, Christina J.; Walsh, Edward P.; Triedman, John K.; Mah, Douglas Y.
Abstract: Introduction: Guidelines recommend trans‐esophageal echocardiography (TEE) for patients with atrial fibrillation (AF) or atrial flutter (AFL) for >48 h, due to risk of intracardiac thrombus formation. With growing evidence that AFL in adults with structurally normal hearts has less thrombogenic potential compared to AF, and the need for TEE questioned, we compared prevalence of intracardiac thrombus detected by TEE in pediatric and congenital heart disease (CHD) patients presenting in AF and AFL. Methods/Results: Single‐center, cross‐sectional analysis for unique first‐time presentations of patients for either AF, AFL, or intra‐atrial reentrant tachycardia (IART) between 2000 and 2019. Patients were categorized by presenting arrhythmia (AF vs. AFL/IART), with the exclusion of other forms of atrial tachycardia, hemodynamic instability, chronic anti‐coagulation before TEE, and presentation for a reason other than TEE examination for thrombus. A total of 201 patients had TEE with co‐diagnosis of AF or AFL. Of these, 105 patients (29 AF, 76 AFL) met inclusion criteria, with no difference in age between AF (median 24.9 years; IQR 18.6–38.3 years) and AFL/IART (23.3 years; 15.4–38.4 years). The prevalence of thrombus in the entire cohort was 9.5%, with no difference between AF (13.8%) and AFL groups (7.9%), p = .46. Patients with thrombus demonstrated no difference in age, systemic ventricular function, cardiac complexity, or CHADS2/CHA2DS2VASc score at presentation. Conclusions: The risk for intracardiac thrombus is high in the pediatric and CHD population, with no apparent distinguishing factors to warrant a change in the recommendations for TEE, with all levels of cardiac complexity being at risk for clot.